Nima Bassiri, Madness and Enterprise: Psychiatry, Economic Reason, and the Emergence of Pathological Value - Drakopoulos, Stavros A (Social History of Medicine, 2024)
The debate regarding the relationship of economics to psychology and related fields has intensified in the last couple of decades. This is mainly due to the rise of behavioural economics which—contrary to mainstream economics—openly claims to pay attention to psychological findings to enrich economic theory and to provide more realistic policy advice.1 One can broadly classify Nima Bassiri’s latest book in this framework. Still, there is an important difference: Bassiri’s work employs an almost reverse point of view in the sense that he studies the impact of economic ideas, concepts and tools on psychiatry. It focuses on the history of psychiatry in the nineteenth century, and more specifically on how psychiatrists felt compelled to diagnostically approach mental illness (madness) through an economic lens. In other words, it examines how psychiatry has used economic reasoning for diagnostic purposes.